NO3 and N2O5 chemistry at a suburban site during the EXPLORE-YRD campaign in 2018. (1st March 2020) - Wang, Haichao; Chen, Xiaorui; Lu, Keding; Hu, Renzhi; Li, Zhiyan; Wang, Hongli; Ma, Xuefei; Yang, Xinping; Chen, Shiyi; Dong, Huabin; Liu, Ying; Fang, Xin; et al.
Abstract: During the EXPLORE-YRD campaign (EXPeriment on the eLucidation of the atmospheric Oxidation capacity and aerosol foRmation, and their Effects in Yangtze River Delta) in May–June 2018, we measured N2 O5, NO2, O3 and relevant parameters at a regional site in Taizhou, Jiangsu Province. The nocturnal average NO3 production rate was 1.01 ± 0.47 ppbv h −1, but the mixing ratio of N2 O5 was low, with a maximum of 220 pptv in 1 min, suggesting rapid loss of NO3 and N2 O5 . The nocturnal steady-state lifetime of N2 O5 was 43 ± 52 s on average, which may be attributed to the elevated monoterpene and fast N2 O5 uptake. VOCs (mainly monoterpenes) dominated daily NO3 loss with the percentage of 36.4% and N2 O5 uptake accounted for 14.4%, when taking NO + NO3 and NO3 photolysis into consideration. We demonstrated that the nonnegligible daytime NO3 oxidation of monoterpene in YRD region, which contributes to the daytime formation of organic nitrate and secondary organic aerosol. The daily average NO x consumption rate via rapid NO3 reaction reached 0.63 ppbv h −1, corresponding to 57.3% NO x loss in comparison with the OH oxidation pathway at this site, highlighting the key role of NO3 and N2 O5 in NO x removal and subsequent photochemistry in the YRD region. Highlights: Low N2 O5 was observed with a nocturnal NO3 production rate of 1.01 ± 0.47 ppbv h −1 . Rapid losses of NO3 and N2 O5 attributed to high monoterpenes and fast N2 O5 uptake. NO3 and N2 O5 chemistry was responsible for more than half of daily NO x removal.